A study on variation in dissolved silica concentration in groundwater of hard rock aquifers in Southeast coast of India - Pradeep, K.; Nepolian, M.; Anandhan, P.; Chandran; Kaviyarasan, R.; Prasanna, Mohan Viswanathan; Chidambaram, S. (2016)
Ground water of hard rock aquifers due to its lesser permeability results in the increased residence time, which leads to the higher concentration of ions. Hence in order to understand the hydro-geochemistry of the groundwater of a hard rock aquifer in India, 23 groundwater samples were collected from different locations of the study area and subjected to analysis of major cations and anions. The results of silica showed different range of concentration and was plotted in different groups. In order to understand the reason for this variation, different techniques like Thermodynamics, Statistics and GIS were adopted and it was inferred that the concentration was mainly governed by lithology and land use pattern of the study area.